Reduction of unnecessary antibiotic days in a level IV neonatal intensive care unit - Dipen P. Vyas; Vilmaris Quinones-Cardona; Margaret A. Gilfillan; Megan E. Young; Kimberly A. Pough; Alison J. Carey (Antimicrobial Stewardship & Healthcare Epidemiology, 2022)
Abstract